Beam-Switch Wide-Swath Mode for Interferometrically Compatible Single-Pol and Quad-Pol SAR Products - Bordoni, Federica; Lopez-Dekker, Paco; Krieger, Gerhard (IEEE Geoscience and Remote Sensing Letters, 2018)
Future spaceborne synthetic aperture radar (SAR) systems are expected to deliver enormous quantity of data. Accordingly, the observation plan becomes crucial for a proper allocation of the mission resources. A central challenge is to reduce the number of acquisitions by making the same image available for more applications. Here, a relevant restriction is the interferometric incompatibility between fully polarimetric (QP) and single polarimetric (SP) SAR images, which typically occurs when the acquisitions are performed in burst mode, as in case of SAR products with wide coverage acquired by means of ScanSAR or terrain observation by progressive scanning (TOPS) technique. In order to overcome this limitation, a new operational mode, denoted as beam-switch wide-swath (BSWS), was conceived. The BSWS mode exploits the operational flexibility of future SAR systems to generate SP images, interferometrically compatible with the QP ones, keeping the wide coverage characteristic of the SP products. This letter presents in detail the BSWS mode, analyzing its functional principle, and imaging performance, based on a realistic future SAR system, the high-resolution wide-swath (HRWS) SAR, considered for the next generation of the Sentinel-1 mission.
Keywords: multichannel Synthetic Aperture Radar (SAR); Digital Beamforming (DBF); High-Resolution Wide-Swath (HRWS); Interferometry